2021
DOI: 10.1002/jgc4.1401
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of genetic counselor practices in inpatient care settings

Abstract: Rapid genomic testing is increasingly used in inpatient settings for diagnostic and treatment purposes. With the expansion of genetic testing in this setting, requests for inpatient genetics consultations have increased. There have been reports of genetic counselors working in inpatient care, though their specific roles are not well described. In this study, we characterized the roles of genetic counselors practicing in inpatient care settings in the United States and Canada. Genetic counselors were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 24 publications
4
11
0
Order By: Relevance
“…In many cases, it allowed them to practice at the top of their scope, maximizing the use of their diverse and advanced board-certified skill set due to the fast-paced, stressful nature of the environment. Although specific information was not obtained about the independence of each participant's role in our study, our companion study by Magness et al (2021) found that 16.1% of inpatient GCs worked independently, without the supervision of a physician, a quality desirable to many GCs (Cohen and Tucker 2018;PSS, 2020) Participants in our study expressed that the spontaneity of consults, the variability of patient indications in the inpatient setting, and the challenge of preparing for consults quickly, kept the work exciting and feelings of burnout lower. In general, GCs have been shown to experience compassion fatigue and burnout (Bernhardt et al 2009;Cohen et al 2017;Cohen & Tucker, 2018) due to the emotionally taxing patient indications seen in genetics (Attard et al, 2019;Fennell et al 2020).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In many cases, it allowed them to practice at the top of their scope, maximizing the use of their diverse and advanced board-certified skill set due to the fast-paced, stressful nature of the environment. Although specific information was not obtained about the independence of each participant's role in our study, our companion study by Magness et al (2021) found that 16.1% of inpatient GCs worked independently, without the supervision of a physician, a quality desirable to many GCs (Cohen and Tucker 2018;PSS, 2020) Participants in our study expressed that the spontaneity of consults, the variability of patient indications in the inpatient setting, and the challenge of preparing for consults quickly, kept the work exciting and feelings of burnout lower. In general, GCs have been shown to experience compassion fatigue and burnout (Bernhardt et al 2009;Cohen et al 2017;Cohen & Tucker, 2018) due to the emotionally taxing patient indications seen in genetics (Attard et al, 2019;Fennell et al 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Participants were recruited from respondents to a quantitative survey study on inpatient genetic counseling by Magness et al (2021). This quantitative study recruited participants from the National Society of Genetic Counselors (NSGC) via the NSGC forum, which had over 4,000 NSGC members as subscribers at the time of survey distribution (NSGC Professional Status Survey (PSS), 2020).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of GCs is increasing at a more rapid rate than geneticist colleagues, it is unknown if this rate is high enough to support the rising demand for these services in the critical care setting (Information on Genetic Counselor and Medical Geneticist Workforces, Report to Congressional Committees, 2020). Inpatient genetic counseling is an emerging area of practice, although not all GCs who provide this service have protected time to provide this care and many provide outpatient care while also being on call (Magness et al, 2021). The impact of this model on quality of patient care and burnout has not been explored, although one may suspect that providing protected time for GCs providing inpatient care would be helpful for both enhancing quality patient care and reducing burnout.…”
Section: Discussionmentioning
confidence: 99%